Extraction of Tsunami Signals from Coupled Seismic and Tsunami Waves - Linjian Song; Chao An (Journal of Marine Science and Engineering)
The generation of an earthquake and a tsunami is a coupled process of radiating seismic waves and exciting tsunamis, and the two types of waves are simultaneously recorded by ocean-bottom pressure sensors. In order to constrain the earthquake source and evaluate the tsunami hazards, it is necessary to separate the tsunami waves. It is traditional to apply a low-pass filter such that the seismic waves are filtered and the tsunami waves remain. However, filtering may also cause distortion of the tsunami waves. In this study, we first use the finite-element method to simulate the generation of seismic and tsunami waves and show that the coupling is a linear superposition of the two waves. We then propose a new method to extract the tsunami waves. First, a low-pass filter with relatively high cutoff frequency that does not affect the tsunami waves is adopted, so that only tsunami waves and low-frequency seismic waves remain. The low-frequency seismic waves satisfy a theoretical equation <semantics>p=ρha</semantics> (p pressure, <semantics>ρ</semantics> water density, h water depth, and a seafloor vertical acceleration), and they can be predicted and removed by utilizing the records of ocean-bottom acceleration. We demonstrate the procedure by numerical simulations and show that the method successfully extracts clean tsunami signals, which is important for earthquake source characterization and tsunami hazard assessment.